Pengaruh Edukasi Gizi Seimbang Terhadap Tingkat Pengetahuan dan Sikap Pemilihan Jenis Makanan Siswa di Sekolah Bola ASIFA (Aji Santoso International Football Academy) Kota Malang - Khairunnisa, Nadhira Hasna; Nurmayanti, Rani; Hapsari, Indri (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Specialized food services cater to specialized training centers or institutions, such as sports training centers. ASIFA is a sports training center with an average age of 13 - 18 years old that provides dormitories and organizes food with 1 day feeding 3 times. Food presentation is done in a buffet so that students can choose and take according to taste. Preliminary studies conducted at ASIFA obtained from the results of interviews with 30 students, it was found that students still consumed food according to their habits and preferences so that food intake did not meet balanced nutrition. This study aims to determine the effect of balanced nutrition education on the level of knowledge and attitude towards choosing the type of food of students. Pre-experimental research with a one group pre-post test design was conducted. The sampling used was purposive sampling as many as students who were in the ASIFA Ball School dormitory, Malang City. The results of the paired sample t-test statistical test at the 95% confidence level, obtained a Sig value. (2-tailed) is 0.000 (<0.05). The results of the Wilcoxon statistical test, obtained a Z value of -3.677 and a Sig value. (2-tailed) 0.000 (<0.05). The results showed that there was an effect of balanced nutrition education on the level of knowledge and attitude towards choosing the type of food for students at the ASIFA (Aji Santoso International Football Academy) soccer school in Malang City.